Old Mice Epididymal Sperm Quality After Short Term Gavage of Cogon Grass Root Ethanol Extract (Majalah Kedokteran Bandung, 2018)
Cogon grass (Imperata cylindrica) has been known as traditional herb because of its antioxidant activity. The oxidant level in the body increases linearly with age. Antioxidant works by decreasing the vulnerability of mammalian spermatozoa towards free radical attack. This study aimed to determine whether the active compound of Imperata cyclindrica root extract improved or damaged  sperm function in old mice. This was a complete randomized study performed in the Mouse Animal Laboratory Faculty of Medicine, Universitas Padjadjaran during the period of August to December 2017. This study was carried out by oral administration of three different doses i.e 115, 230, and 345 mg/kg body weight of cogon grass root ethanol extract into 24- weeks-old DDY strain mice for 14 days. Results showed no significant difference in body weight  and testicular index before and after treatment (p
Keywords: Aging; Imperata cylindrica; sperm quality